2015
DOI: 10.1039/c5nr04608d
|View full text |Cite
|
Sign up to set email alerts
|

Polarization-dependent extraordinary optical transmission from upconversion nanoparticles

Abstract: Enhanced upconversion (UC) emission was experimentally demonstrated using gold double antenna nanoparticles coupled to nanoslits in gold films. The transmitted red emission from UC ytterbium and erbium co-doped sodium yttrium fluoride (NaYF4:Yb(3+)/Er(3+)) nanoparticles (UC NPs) at ∼665 nm (excited with a 980 nm diode laser) was enhanced relative to the green emission at ∼550 nm. The relatively enhanced UC NP emission could be tuned by the different polarization-dependent extraordinary optical transmission mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Upconversion is a non‐linear optical process which two or more low‐energy near infrared (NIR) photons are absorbed to generate a higher‐energy photon ,. Due to such unique anti‐Stocks luminescent property, lanthanide rare‐earth doped upconversion nanoparticles (UCNPs) exhibited great potential values in the past years in many application fields such as bio‐imaging, optical sensing, lasing, full‐color display, photo dynamic therapy, drug releasing, super‐resolution imaging and anti‐counterfeiting …”
Section: Introductionmentioning
confidence: 83%
“…Upconversion is a non‐linear optical process which two or more low‐energy near infrared (NIR) photons are absorbed to generate a higher‐energy photon ,. Due to such unique anti‐Stocks luminescent property, lanthanide rare‐earth doped upconversion nanoparticles (UCNPs) exhibited great potential values in the past years in many application fields such as bio‐imaging, optical sensing, lasing, full‐color display, photo dynamic therapy, drug releasing, super‐resolution imaging and anti‐counterfeiting …”
Section: Introductionmentioning
confidence: 83%
“…In this context, some other groups also reported the polarized UCL from NaYF 4 , LiYF 4 , and LiLuF 4 UCNPs. [ 107–111 ] To make use of polarized UCL, Paloma et al. reported using microsized upconverting particles (UCP) to monitor the suspending medium in real‐time via single‐particle spectroscopy.…”
Section: Remote Regulation Of Upconversionmentioning
confidence: 99%
“…In this context, some other groups also reported the polarized UCL from NaYF 4 , LiYF 4 , and LiLuF 4 UCNPs. [107][108][109][110][111] To make use of polarized UCL, Paloma et al reported using microsized upconverting particles (UCP) to monitor the suspending medium in real-time via singleparticle spectroscopy. [112] Single UCP was optically trapped and maintained at a certain position, followed by the excitation of linearly polarized 980 nm laser (Figure 10b).…”
Section: Regulating Upconversion By Different Polarization Anglementioning
confidence: 99%
“…Inspired by this pioneering work, several other research groups have also reported the polarized UCL in anisotropic NaYF 4 , LiYF 4 , and LiLuF 4 UCNPs with polarized morphologies like rod, disk and rhombus. [104][105][106][107][108] Moreover, such polarized UCL can also be realized and extended to the macroscale level. By using a shear-driven method, He and coworkers prepared orientationally aligned NaYF 4 :Yb/Gd/Er nanorod arrays, which were characterized with a nematic liquid crystal phase.…”
Section: Enhancing Upconversion Luminescence Through Physical Strategiesmentioning
confidence: 99%
“…Inspired by this pioneering work, several other research groups have also reported the polarized UCL in anisotropic NaYF 4 , LiYF 4 , and LiLuF 4 UCNPs with polarized morphologies like rod, disk and rhombus. 104–108…”
Section: Enhancing Upconversion Luminescence Through Physical Strategiesmentioning
confidence: 99%